The Impact of Perceived Performance Evaluation Formality on Managers' Behavior - Neny Desriani; Mahfud Sholihin (The Indonesian Journal of Accounting Research, 2013)
This study examines the impact of perceived performance  evaluation formality on subordinates' trust in a supervisor with three mediating variables: procedural justice, distributive justice, and feedback quality. In addition, this study examines the impact of a subordinate's trust in a supervisor on budgetary slack. Using a questionnaire survey method with 97 middle and lower level managers in an aerospace company as respondents, this study shows that procedural justice, distributive justice, and feedback quality do not mediate the relationship between the formality of the performance evaluation and subordinates' trust in their supervisors. However, this study  finds that trust can reduce propensity to create budgetary slack.